Tips & tricks for Excel-based financial modeling : a must for engineers & financial analysts. - Mian, M. A. (Mohammed A.) (Finance and financial management collection., 2017)
The purpose of this work is to show some advanced concepts related to Excel based financial modeling. Microsoft Excel (TM) is a very powerful tool and most of the time we do not utilize its full potential. Although not very difficult to use but it needs practice and continuously striving to use the full potential of Excel. Of course, any advanced concepts require the basic knowledge which most of us have and then build on it. It is only by hands-on experimentation that one learns the art of constructing an efficient worksheet. It is hoped that the examples herein will aid the reader to develop his or her own worksheets using advanced concepts. The biggest advantage of Excel is that it is not a black box, especially if you have built the model yourself rather than working with somebody else's model. The basic requirement for most financial modeling is to keep them simple so anyone can look at it can easily figure out how most of the calculations are performed. The two volumes of this book cover dynamic charting, macros, goal seek, solver, the routine Excel functions commonly used, the lesser known Excel functions, the Excel's financial functions, and so on. The introduction of macros in these books is not exhaustive but the purpose of what is presented is to show you the power of Excel, and it can be utilized to automate most repetitive calculations at a click of a button. For those who use Excel on a daily basis in financial modeling and project/investment evaluations, this book is a must. It contains a wealth of practical examples, tips, new techniques all designed to help quickly exploit and master Excel to its full advantage and therefore use spreadsheets more effectively in your jobs.